2019
DOI: 10.1002/glia.23675
|View full text |Cite|
|
Sign up to set email alerts
|

GLIA Porto 2019: Abstracts Oral Presentations, Posters, Indexes

Abstract: Reversible oxidative modifications regulate protein activity. Oxidoreductases such as Glutaredoxin 2 control the thiol redox state of proteins. Here, we demonstrate that Glutaredoxin 2 modifies the cytoskeleton and thereby migration capacity of glia cells. The lack of Glutaredoxin 2 decreases transmigration of mouse primary oligodendrocyte progenitor cells, whereas enhanced levels of Glutaredoxin 2 increase migration. In both, transmigration and scratch closure Glutaredoxin 2 is able to overcome the inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…These evidences were indeed very recently confirmed by the development of a transgenic mouse line, in which the mutation was carried by GLAST-expressing astrocytes solely (Slc1a3 P290R/+ mice). This animal model was shown to suffer from epilepsy, ataxia, and showed cerebellar atrophy, thereby closely resembling the features of EA6 [105]. Specifically, these degenerative effects were unveiled to be triggered by an increased chloride efflux from BG, resulting in BG apoptosis and, subsequently, in a secondary loss of glutamate clearance and cerebellar atrophy.…”
Section: Well Beyond Glutamate Uptake: the Role Of Glast As Ion Channmentioning
confidence: 82%
“…These evidences were indeed very recently confirmed by the development of a transgenic mouse line, in which the mutation was carried by GLAST-expressing astrocytes solely (Slc1a3 P290R/+ mice). This animal model was shown to suffer from epilepsy, ataxia, and showed cerebellar atrophy, thereby closely resembling the features of EA6 [105]. Specifically, these degenerative effects were unveiled to be triggered by an increased chloride efflux from BG, resulting in BG apoptosis and, subsequently, in a secondary loss of glutamate clearance and cerebellar atrophy.…”
Section: Well Beyond Glutamate Uptake: the Role Of Glast As Ion Channmentioning
confidence: 82%
“…Interestingly, in basal conditions, ventral midbrain astrocytes release more EVs than striatal astrocytes. This diversity in the secretion of EVs seems to suggest the existence of specific brain region-linked differences which may have possible functional implications in the intercellular communication within the nigrostriatal area [254]. Moreover, the authors identified a specific subset of miRNAs and proteins enriched in the ventral midbrain astrocyte-derived EVs, with a potential impact on DAergic neuroprotection and NSC differentiation.…”
Section: Non-modified Evs To Arrest the Pathologic Propagation Of Pdmentioning
confidence: 92%
“…Remarkably, besides SHED-EVs, glial-derived EVs may play key roles in both neurodegeneration and neuroprotection in PD experimental models, as recently reviewed by our group [51]. For example, the studies of Leggio and collaborators [254] revealed that astrocytes from the ventral midbrain, which induce nigrostriatal rescue in MPTP-treated mice [23], were able to secrete vesicles in the size range of s-EVs and positive for classical EV markers (e.g., CD63, CD9, Tsg101) [254]. Interestingly, in basal conditions, ventral midbrain astrocytes release more EVs than striatal astrocytes.…”
Section: Non-modified Evs To Arrest the Pathologic Propagation Of Pdmentioning
confidence: 93%